Dr. C.F. Shah and his innovations - Dixit, Mukund R. ([London] : SAGE, 2016)
This case describes the innovations of a medical practitioner over six decades of practice. It provides an opportunity to the participants to analyse the motivation, processes, constraints and outcomes or innovating efforts of individuals as opposed to corporates.
Originally Published in: Dixit, M. R. (2015). Dr. C. F. Shah and his Innovations. BP0384. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; New products -- Case studies; Creative ability in business -- Case studies; Drug development -- Case studies